2006
DOI: 10.1086/503286
|View full text |Cite
|
Sign up to set email alerts
|

The 2005 Outburst of the Halo Black Hole X‐Ray Transient XTE J1118+480

Abstract: We present optical and infrared monitoring of the 2005 outburst of the halo black hole X-ray transient XTE J1118+480. We measured a total outburst amplitude of $5:7 AE 0:1 mag in the R band and $5 mag in the infrared J, H, and K s bands. The hardness ratio HR2 (5 12 keV : 3 5 keV ) from the RXTE ASM data is 1:53 AE 0:02 at the peak of the outburst, indicating a hard spectrum. Both the shape of the light curve and the ratio L X (1 10 keV)/L opt resemble the minioutbursts observed in GRO J0422+32 and XTE J1859+2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
55
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 46 publications
(59 reference statements)
10
55
0
Order By: Relevance
“…The shape of the SED is similar to the one of the transient LMXB XTE J1118+480 (Chaty et al 2003;Zurita et al 2006): although in the LHS during its 2005 outburst, the latter work gave IR and optical slopes with different α values, softening from 0.49 at the peak, not far from our value but distinct, as XTE J1818−245 was in another spectral state, to 0.25 (decay). In the case of the 2000 outburst, the SED of XTE J1118+480 from radio to X-rays has been explained as a combination of synchrotron radiation from a jet and a truncated optically thick disc, whereas models assuming advection dominated accretion flows alone underestimated the optical and IR fluxes (Zurita et al 2006 and references therein).…”
Section: Spectral Energy Distribution (Sed)supporting
confidence: 72%
See 1 more Smart Citation
“…The shape of the SED is similar to the one of the transient LMXB XTE J1118+480 (Chaty et al 2003;Zurita et al 2006): although in the LHS during its 2005 outburst, the latter work gave IR and optical slopes with different α values, softening from 0.49 at the peak, not far from our value but distinct, as XTE J1818−245 was in another spectral state, to 0.25 (decay). In the case of the 2000 outburst, the SED of XTE J1118+480 from radio to X-rays has been explained as a combination of synchrotron radiation from a jet and a truncated optically thick disc, whereas models assuming advection dominated accretion flows alone underestimated the optical and IR fluxes (Zurita et al 2006 and references therein).…”
Section: Spectral Energy Distribution (Sed)supporting
confidence: 72%
“…In the case of the 2000 outburst, the SED of XTE J1118+480 from radio to X-rays has been explained as a combination of synchrotron radiation from a jet and a truncated optically thick disc, whereas models assuming advection dominated accretion flows alone underestimated the optical and IR fluxes (Zurita et al 2006 and references therein). In 2005, discrepancies observed between the optical and IR SEDs suggested that the IR was dominated by a different component (a jet?)…”
Section: Spectral Energy Distribution (Sed)mentioning
confidence: 99%
“…This could potentially result in re-acceleration of particles up to very high energies. In general, the shape of our SEDs during the LHS are similar to the ones of the transient LMXB XTE J1118+480 (Chaty et al 2003;Zurita et al 2006): in its 2000 outburst, the SED from radio to X-rays has been explained as a combination of synchrotron radiation from a jet and a truncated optically thick disc, whereas models assuming advection dominated accretion flows alone underestimated the optical and IR fluxes (Zurita et al 2006, and references therein). Discrepancies observed between the optical and IR SEDs of XTE J1118+480 in 2005 suggested that the IR was dominated possibly by a jet, whereas the optical was dominated by disc emission.…”
Section: Spectral Energy Distributionssupporting
confidence: 59%
“…With an Eddington ratio of LX /L Edd ∼ 10 −8.5 , J1118 is one of our best probes of black hole accretion flows at the lowest detectable luminosities. A special aspect of J1118 is that it has also been well-studied at higher luminosities during previous outbursts (e.g., Esin et al 2001;Markoff, Falcke & Fender 2001;McClintock et al 2001;Hynes et al 2000Hynes et al , 2003Chaty et al 2003;Malzac, Merloni & Fabian 2004;Zurita et al 2006;Maitra et al 2009;Brocksopp et al 2010;Vila et al 2012;Zhang & Xie 2013).…”
Section: Introductionmentioning
confidence: 99%